DATA ANALYTICS FOR FINANCE USING R-PROGRAMMING APPLICATION ; A CASE STUDY ON MEASURING THE IMPACT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY WITH SPECIAL REFERENCE TO TATA MOTORS - Dr.Nitin Jaglal Untwal (International Journal of Advanced Science and Technology, 2020)
The study is about measuring the impact of liquidity and efficiency of working capital on return on investment or Asset in the form of empirical test analysis. The independent variables are liquidity and efficiency ratios of working capital. The dependent variable is return on asset ratio further researcher had used R- programming for analysis. The data frame is prepared in R-programming and loading the data for analysis is done to draw predictive modelling results. The author collected secondary data from Screener data base. Screener is a stock screener and research tool for Indian stocks. Period of study is 2008 -2014 of Tata Motors.